In silico approaches of gandarusa (Justicia gendarussa Burm. f.) potential for osteoporosis prevention via EGF pathway - Sri Dinengsih; Nurdiana; Sri Winarsih; Bambang Raharjo; Agustina Tri Endharti (GarVal Editorial Ltda., 2024)
Context: On a cellular level, osteoporosis is a metabolic bone disease caused by osteoclastic bone resorption that is not offset by osteoblastic bone synthesis. This increases the risk of fractures by making bones weak and brittle. The selective inactivation of the epidermal growth factor receptor (EGFR) in osteoblast lineage cells demonstrated that EGFR promotes bone formation by increasing the number of mesenchymal progenitors. Active compounds of gandarusa (Justicia gendarussa Burm. f.) are potentially playing crucial roles in EGFR activation. Aims: To evaluate the potential of J. gendarussa for osteoporosis prevention via EGF pathway in silico. Methods: A GC-MS approach was used to screen the active compounds from 70 and 95% methanol extraction, which was continued with molecular docking analysis by PyRx v0.8. The visualization and amino acid interactions were also revealed using Discovery Studio software R17. ADME analysis was performed using the SwissADME webserver to consider whether the best compound could be classified as a drug following Lipinsky rule's of five. Results: The top five compounds with high binding affinity were selected from a total of 33 active compounds detected. One compound, namely eslicarbazepine, has a -6.7 kcal/mol affinity score and passes the threshold for drugs bioavailability, supported by the data of MW compounds 254.28 kDa, low rotatable bonds 1 bond, hydrogen bond acceptors and donors (2), high GI absorption, and ability to permeant to blood-brain barrier system. Conclusions: This finding added new insight into J. gendarussa extract potential as anti-osteoporosis in humans. Nevertheless, in vitro and in vivo experiments are necessary to confirm the potential.